CHLORINE CONTENTS AND BACTERIOLOGICAL QUALITY OF SWIMMING POOLS WATER IN JAYAPURA - Fajar Bakti Kurniawan; Yulianus Wima Krisna Alfreda; Asrianto Asrianto; Indra Taufik Sahli; Meidy J Imbiri; Risda Hartati; Rina Purwati; Afika H Wardhani; Loly Sabrina Sitompul (POLTEKKES KEMENKES JAYAPURA, 2022)
Chlorine is a chemical that functions as water disinfection, often used in swimming pools to kill microorganisms such as pathogenic bacteria in the water. The general objective of this study was to determine the relationship between chlorine levels, and microbiological quality in swimming pool water in Jayapura City. This type of research is descriptive research with a cross-sectional design. Determination of residual chlorine content, and microbiological quality in this study was carried out using Spectrophotometry, and MPN Test methods. The results showed that the chlorine content of the swimming pool Wa 5.00 mg/l, Fu 0.23 mg/l, and Aj 0.13 mg/l. The examination of the coliform bacteria population showed that the MPN value in Wa coliform swimming pool water was 0/100 ml, and coliform stools were 0/100 ml. Swimming pool Fu coliform as much as 91/100 ml, and fecal coliform as much as 23 /100 ml. Swimming pool Aj coliform as much as >1100/100 ml, and fecal coliform as 20/100 ml. This study concludes that the chlorine levels in the Wa swimming pools, and the MPN swimming pools of Fu, and Aj are not under the Minister of Health Regulation No. 32 years 2017. Keywords : Coliform, Swimming pool, MPN